Pemberdayaan Masyarakat Melalui Pengembangan Objek Wisata Dan Optimalisasi Pemanfaatan Media Sosial Dalam Promosi Wisata Sontoh Laut Surabaya - Etty Widawati; Syamsul Arifin; Affrilian Andi Pranata; Ainun Haqiqi Sri Mustika (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This Community Service is carried out with the aim of providing a real picture of the application or implementation of the knowledge that has been obtained in lectures and comparing it with conditions in the field and increasing student knowledge in overcoming problems in the community and also providing benefits to increase student knowledge in learning new things related with the community and marine sontoh sea tourism. The method used in community service activities is by conducting an initial survey regarding the potential of the selected tourism as the location of the PKM, determining the right time for the implementation of the PKM, coordinating with Pokdarwis regarding the work program to be carried out, direct socialization to the community. The results obtained from community service activities that focus on developing tourist objects by adding infrastructure that can be useful to attract tourists and MSMEs, so as to increase sales and human resources. Based on the results of observations and discussions the Pkm Surabaya 3 team has compiled a work program as follows, namely an introduction to tourism video with the aim of helping to show the characteristics of marine marine tourism, reforestation which is useful for making the marine sontoh marine tourism environment more beautiful, signposts are made to make it easier the tourists go to the marine tourism location of Sontoh Laut, photo spots with the aim of providing the beauty of the place, so that tourists when visiting are interested in taking pictures, socializing with the aim of adding insight to the surrounding community and maintaining existing cultural values so that they become characteristics and characteristics from marine tourism to sontoh laut, and finally an additional program, namely teaching the Koran and English.